2002
DOI: 10.1152/ajpheart.00693.2001
|View full text |Cite
|
Sign up to set email alerts
|

Acute exercise enhances vasorelaxation by modulating endothelial calcium signaling in rat aortas

Abstract: The role of endothelial calcium signaling in exercise-enhanced ACh-induced vasorelaxation was examined using male Wistar rats (8∼10 wk old) that were divided into control and exercise groups. The exercised animals ran on a treadmill with progressive increments of speed until exhaustion. After decapitation, aortic rings were dissected and loaded with fura 2-AM. After being mounted on a tissue flow chamber, vessels were precontracted with phenylephrine, and ACh-induced endothelial calcium elevation and vasorelax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 28 publications
5
17
0
1
Order By: Relevance
“…24,25) A single bout of aerobic exercise is well known to enhance vascular endothelial function, resulting in improvement of peripheral blood flow. [26][27][28] These reports support our hypothesis that the stretching exercises improved NO-dependent vasodilation in arterioles and capillaries, resulting in increased peripheral blood flow through these vessels.…”
Section: Discussionsupporting
confidence: 80%
“…24,25) A single bout of aerobic exercise is well known to enhance vascular endothelial function, resulting in improvement of peripheral blood flow. [26][27][28] These reports support our hypothesis that the stretching exercises improved NO-dependent vasodilation in arterioles and capillaries, resulting in increased peripheral blood flow through these vessels.…”
Section: Discussionsupporting
confidence: 80%
“…21) A previous animal study found that a single session of exercise using a treadmill increased calcium influx and calcium-dependent nitric oxide release in the vascular endothelium and then enhanced vasodilation. 22) Moreover, aerobic exercise of the lower limbs using a cycle ergometer has been reported to augment vessel shear stress in not only the lower limbs, but also upper limbs in healthy people. 23) Therefore, a single session of NMES with muscle contraction is considered to induce nitric oxide-dependent vasodilation via the augmentation of vessel shear stress, even in the upper limbs, resulting in enhanced vascular endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings show that one bout of moderate-intensity exercise is able to attenuate vasoconstrictor response to NE and KCl in rat aorta, and also to increase vascular nitrite and nitrate concentrations. While some studies have already shown that there is an improvement on endotheliumdependent vasodilator response after a bout of exercise Jen et al, 2002;Goto et al, 2007), there is still a controversy about the acute effect of exercise on vasoconstrictor response to norepinephrine. In the present study, we observed an important decrease on adrenergic vasoconstriction after a bout of moderate-intensity exercise.…”
Section: Discussionmentioning
confidence: 99%
“…It has already been observed that the acute exposure of endothelial cells and rat aorta to both increased shear stress (Corson et al, 1996;Harrison et al, 2006) and high levels of adrenergic agonists (Gürdal et al, 2005) is able to enhance the activity and expression of this enzyme. Furthermore, exercise is also able to increase the endothelial calcium influx and the calciumdependent nitric oxide release (Jen et al, 2002). Although we did not evaluate directly the eNOS activity in our experimental model, we suggest that it might be increased after the bout of exercise performed, since the pre-incubation with L-NAME shows a higher increase in the developed tension by the exercise group compared with control group on the concentration-response curves to NE (31% vs. 7%, respectively) and KCl (29% vs. 16%, respectively).…”
Section: Discussionmentioning
confidence: 99%